READERS BATTALION IN ABDUL RAHMAN BIN ALASHAATH ARMY - Sayah Al Essa, Mohammad (European Scientific Journal, ESJ, 2015)
Abdul Rahman bin Alashaath revolution was considered one of the most important and most dangerous revolutions in the Umayyad period, even though it was not doctrinal. This revolution started from the eastern borders of the Islamic state against Iraq. Wali Al-Hajjaj bn Yusuf Thaqafi rose up and took over from Al Khalifa Abdul Malik bin Marwan. What distinguishes this revolution share readers of the people of Iraq in addition to a large number of loyalists who were indignant by the economic and social conditions? Readers played an important role in the revolution and they were able to achieve many victories. However, Al-Hajjaj managed to defeat them at the Battle of Deir Al-jamajem and abolish their revolution.